2015
DOI: 10.1155/2015/365854
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Exerts Cardioprotective Effects through Improving Sarcoplasmic Reticulum Ca2+-ATPase Activity in Rats during Ischemia/Reperfusion In Vivo

Abstract: The flavonoid luteolin exists in many types of fruits, vegetables, and medicinal herbs. Our previous studies have demonstrated that luteolin reduced ischemia/reperfusion (I/R) injury in vitro, which was related with sarcoplasmic reticulum Ca2+-ATPase (SERCA2a) activity. However, the effects of luteolin on SERCA2a activity during I/R in vivo remain unclear. To investigate whether luteolin exerts cardioprotective effects and to monitor changes in SERCA2a expression and activity levels in vivo during I/R, we crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Our previous studies have demonstrated that Lut can protect the myocardium from I/R injury by down-regulating microRNA-208b-3p [17] and the PI3K/Akt pathway [18]. Moreover, decreased expression and activity of SERCA2a can be partly reversed by Lut [19, 20]. These studies provide evidence that Lut has a protective effect on heart.…”
Section: Introductionmentioning
confidence: 71%
“…Our previous studies have demonstrated that Lut can protect the myocardium from I/R injury by down-regulating microRNA-208b-3p [17] and the PI3K/Akt pathway [18]. Moreover, decreased expression and activity of SERCA2a can be partly reversed by Lut [19, 20]. These studies provide evidence that Lut has a protective effect on heart.…”
Section: Introductionmentioning
confidence: 71%
“…Lut group were fed with Lut administration (10 ug/Kg/d, ip)48 for 14d. Lut + LY group were fed with Lut administration (10 ug/Kg/d, ip) and LY administration (0.3 mg/Kg/d, ip)19 for 14d. Lut + LY + TG group were fed with Lut administration (10 ug/Kg/d, ip) and LY administration (0.3 mg/Kg/d, ip) for 14d, and subjected to SERCA2a inhibitor TG (1 mg/kg/d, ip) on the twelfth day47.…”
Section: Methodsmentioning
confidence: 99%
“…The protein expression was examined by western blot analysis as previously described1619. Total protein was harvested from cultured cells or myocardium tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study found that Lut improved SERCA2a activity partially through activation of the PI3K/AKT signaling pathway and increased the phosphorylation of AKT (p-Akt) at amino acids 308 and 473 levels, but did not change the SERCA2a expression at protein levels. The infarct size, pro-apoptosis proteins, and lactate dehydrogenase release (LDH) release were reduced by Lut during I/R injury in vivo ( Nai et al, 2015 ), and the same effects were seen in diabetic rats ( Sun D. et al, 2012 ).…”
Section: Introductionmentioning
confidence: 96%